2015
DOI: 10.1590/0103-8478cr20141305
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ensiling and haymaking on the concentrations of steroidal saponin in two Brachiaria grass species

Abstract: Brachiaria (signalgrass) is now the most widely used tropical grass genus in Central and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…Since making hay reduces protodioscin content [ 29 ], using the grasses in the form of hay could be an alternative in order to avoid saponin toxicosis. Also, it would be interesting to consider the use of other grasses for cattle growing, particularly native grasses previously tested to verify that they do not accumulate saponins or other potentially toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Since making hay reduces protodioscin content [ 29 ], using the grasses in the form of hay could be an alternative in order to avoid saponin toxicosis. Also, it would be interesting to consider the use of other grasses for cattle growing, particularly native grasses previously tested to verify that they do not accumulate saponins or other potentially toxic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Ferreira et al [134] found a strong relationship between saponin concentration on young leaves and hours of solar radiation. Ensiling B. decumbens has been shown to decrease protodioscin concentrations significantly (2.28 mg/g DM to 0 mg/g DM) over 20 days while conserving B. decumbens as hay only reduced protodioscin concentration by 48% [135]. There is no clear trend in saponin concentration with plant age per se [76,105,122], with higher concentrations found in plant material 60 days of age or younger but almost stable levels over the following 300 days [105,122].…”
Section: Identification and Metabolism Of Toxic Compoundsmentioning
confidence: 99%
“…Subsequently, it was demonstrated that poisoning in ruminants was caused by steroidal saponins (Brum et al, 2007). Protodioscin, a saponin present in plants of the Brachiaria genus, may cause liver lesion and, subsequently, photosensitization (Riet-Correa et al, 2011, Lima et al, 2015. Leal et al (2020) observed the protodioscin contents of five Brachiaria brizantha cultivars: arapoty, paiaguas, xaraes, and marandu palisadegrass, and piata throughout the year in all seasons.…”
Section: Introductionmentioning
confidence: 99%